2013
DOI: 10.1161/hypertensionaha.111.00690
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Prognostic Value of White Coat Hypertension

Abstract: Abstract-The prognostic value of white coat hypertension (WCH) is still debated. In 2051 subjects representative of the general population of Monza, we measured office, ambulatory, and home blood pressure (BP). The risk of cardiovascular and allcause mortality was assessed over 16 years in normotensive, sustained hypertensive, and WCH subjects, the last group being defined as usually done in clinical practice (ie, by normality of 1 out-of-office [ambulatory or home] BP with an office BP elevation). Compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
70
2
6

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(81 citation statements)
references
References 16 publications
3
70
2
6
Order By: Relevance
“…No difference in renal function between WCHT and HT patients was noted by Pierdomenico et al [26] . In the PAMELA study, Cardillo, Weber, Mancia and Mulè reported that LVMI was increased in WCHT patients compared with NT patients (P < 0.01), whereas Pierdomenico and Hoeghelm found no difference in LVMI [5,[26][27][28][29][30][31] . Arterial compliance was lower in WCHT patients than in the NT group in studies by Karter's (P < 0.001) and Gomez [25,32] .…”
Section: Prognosis and Stroke Risk In Patients With White-coat Hypertmentioning
confidence: 94%
“…No difference in renal function between WCHT and HT patients was noted by Pierdomenico et al [26] . In the PAMELA study, Cardillo, Weber, Mancia and Mulè reported that LVMI was increased in WCHT patients compared with NT patients (P < 0.01), whereas Pierdomenico and Hoeghelm found no difference in LVMI [5,[26][27][28][29][30][31] . Arterial compliance was lower in WCHT patients than in the NT group in studies by Karter's (P < 0.001) and Gomez [25,32] .…”
Section: Prognosis and Stroke Risk In Patients With White-coat Hypertmentioning
confidence: 94%
“…There may not be a significant effect on reducing clinical (the magnitude of the white coat effect remains) or self-measured or ambulatory BP values (if they were already within normal limits). In this respect, the study by Mancia et al 8 could help to establish a pattern. According to the study, a diagnosis of white coat hypertension would require both measurements (at home and in an ambulatory setting) to be taken and to be normal.…”
mentioning
confidence: 96%
“…9 The second important aspect refers to the artificial categorization of continuous variables with a continuous relationship to the incidence of complications. In this respect, the data provided by Mancia et al 8 show that patients classified as presenting with white coat hypertension have BP values that are midway between hypertensive and normal. This is true for clinical and also for self-measured and 24-hour values.…”
mentioning
confidence: 99%
“…In addition, studies have shown that white coat hypertension may not be "benign" and is associated with increased longterm risk of cardiovascular morbidity. 3,4 Home and 24-hour ambulatory BP monitoring in young adults with mildly elevated office BP may contribute to the early identification and treatment of hypertension.Future studies on designing health care interventions for timely and improved management of hypertension in young adults should focus on the use and effectiveness of life-style modifications; and the patients' and providers' knowledge, attitudes, beliefs and practices toward management of office readings of high BP. Patient and provider education; practice-specific design algorithms for the management of hypertension, including use of ambulatory BP monitoring; and computer alerts targeting multiple high BP readings on a given patient across different practice contact points such as primary or specialty care, have the potential to improve hypertension management in general, as well as in young adults in particular.…”
mentioning
confidence: 99%
“…In addition, studies have shown that white coat hypertension may not be "benign" and is associated with increased longterm risk of cardiovascular morbidity. 3,4 Home and 24-hour ambulatory BP monitoring in young adults with mildly elevated office BP may contribute to the early identification and treatment of hypertension.…”
mentioning
confidence: 99%